Why There is Still an Illicit Trade in Cultural Objects and What We Can Do About It. (17th February 2022) - Brodie, Neil; Kersel, Morag M.; Mackenzie, Simon; Sabrine, Isber; Smith, Emiline; Yates, Donna
ABSTRACT: Fifty years after the adoption of the 1970 UNESCO Convention, the illicit trade in cultural objects endures, with harmful consequences to local communities, knowledge acquisition, and archaeological landscapes and objects. In this article, we present a gap analysis to assess under-performing policy and practice. We argue that a poor understanding of how the trade is organized and operates and of how it might be regulated hinders effective policy formulation. Funding structures which encourage short-term ad hoc research and inhibit information sharing are in part responsible for some of the gaps. We conclude by suggesting how sustained theoretically informed, evidence-led collaborative analyses might help reduce or mitigate these problems, preventing another 50 years of illicit trade.